2020
DOI: 10.16926/par.2020.08.25
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of the kick start from OSB12

Abstract: Introduction: Start performance in swimming plays a major role in determining the final standings, especially in sprint races. The purpose of the study was to determine kinematic parameters underlying the kick start from OSB12 in terms of the kick plate position and shoulder positioning at the start. Material and methods: The sample included 8 non-randomly recruited performance-level swimmers whose average age, body height, and body weight was 17.4 ± 1.8 years, 182.2 ± 3.4 cm and 81.00 ± 3.9 kg, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A study by Shepherd et al [ 7 ] demonstrated that rebounding body position does not differ for the two genders but is a critical factor in determining initial performance for both genders. Barlow et al [ 1 ] and Matúš and Kandráč [ 5 ] reported the best performance when the kick plate is at the third and fourth level, respectively. Starting performance is also influenced, to some extent, by experience gained during previous practice [ 22 ], and regular training can improve the engagement of motor units [ 23 ] that can influence starting performance, especially during take-off from the start block, where the swimmer can reach twice the speed as opposed to swimming [ 13 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Shepherd et al [ 7 ] demonstrated that rebounding body position does not differ for the two genders but is a critical factor in determining initial performance for both genders. Barlow et al [ 1 ] and Matúš and Kandráč [ 5 ] reported the best performance when the kick plate is at the third and fourth level, respectively. Starting performance is also influenced, to some extent, by experience gained during previous practice [ 22 ], and regular training can improve the engagement of motor units [ 23 ] that can influence starting performance, especially during take-off from the start block, where the swimmer can reach twice the speed as opposed to swimming [ 13 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The better performance achieved in the preferred base position may also be due to a psychological effect or the result of prolonged motor learning in the kick starts. On the other hand, a preferred backrest setup on an OSB or OSB platform may lead to a shorter take-off performance, but the basic position on the start block before the take-off is still crucial [ 5 , 8 , 9 ]. Therefore, we can distinguish three basic positions in the base position on the start block-front-, neutral-, and rear-weighted [ 1 , 15 , 25 , 26 ], with neutral-weighted and weighted being confirmed in some studies [ 1 , 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Performance of all specific movements is in direct relationship with spatial transfer of extremity segments. A well-defined biomechanical structure is envisaged in the organization of contraction of some or another muscle [8,9,20,21,22]. All specific movements, whose structure includes flexionextension of segments of the lower extremities, provide for movement in the sagittal plane, abduction-adduction in the frontal plane or other ones parallel to them [3].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that there must be a balance between block time and horizontal velocity [24]. In a study by Matúš et al [33], swimmers with the shortest block times did not produce the shortest times to 5 m. Swimmers produced the shortest block times when using the front-weighted kick start. However, the shortest times to 5 m were found for the rear-weighted kick start.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, shorter reaction times may negatively affect these values. Research studies by Matúš et al [33,34] aimed at the grab, track, or kick start or their modifications showed that the swim start during which swimmers produced shorter reaction times did not result in shorter times to 5, 7.5, and 10 m, respectively. In general, we conclude that production of shorter reaction times without losing horizontal velocity may be achieved by using a new OSB starting block.…”
Section: Discussionmentioning
confidence: 99%